Peran Amandemen UUD 1945 Dalam Memperkuat Sistem Check And Balance - Herlinanur, Nanda; Pangestoeti, Wahjoe; Putra, Adrian Kurnia Sobana; Rahim , Rafidah (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This research analyzes the impact of the amendments to the 1945 Constitution on the check and balance system in Indonesia. The constitutional amendments were made to adjust and strengthen the country’s legal framework, enhance democracy, and improve government accountability and transparency. This study uses a doctrinal juridical approach, focusing on the analysis of legal norms contained in the 1945 Constitution and relevant legal literature. The research methodology involves the exploration and analysis of primary and secondary legal literature, normative analysis, legal interpretation, and a combination of analyses to produce comprehensive conclusions. The results show that the amendments to the 1945 Constitution successfully strengthened the check and balance system through significant changes in the distribution of power and relationships between state institutions. The People’s Consultative Assembly (MPR) experienced a power reduction, while the House of Representatives (DPR) gained a central role in legislation. The establishment of the Regional Representative Council (DPD) strengthened regional representation. Additionally, the President and Vice President are elected directly by the people with term limits to prevent the concentration of power. The Supreme Court (MA) and the Constitutional Court (MK) were strengthened to maintain judicial independence and uphold law and justice. This research identifies challenges in the implementation of the amendments, including structural and cultural barriers. Recommendations include enhancing political education, strengthening legal institutions, and improving coordination between state institutions. With these amendments, it is hoped that the Indonesian government will become more stable, effective, and efficient in achieving the nation’s goals. The amendments to the 1945 Constitution reflect a commitment to establishing a more democratic and just government with a stronger and more accountable check and balance system.